A Review of the History of Children’s Literature in Iran, from Pre-Islam to the Present - Sawaedi, Adel (International Journal of Psychosocial Rehabilitation, 2020)
The present paper analyzes the state of children’s literature in Iran from the Pre-Islamic times to the present. In this regard, it is worth mentioning that although according to the current definition, the cornerstone of children’s literature in Iran has been laid during the constitutional period and has grown and flourished in recent decades, the pre-constitutional literary context was not devoid of children-related works in accordance with the socio- educational structure. Apparently in Iran, children, the main audience of folk literature, were provided with only oral literature, lullabies, songs, and adult literature. But over time, through intellectual growth of Iranian society, the child, who had been less notable in official literature, possessed his own literature which didn’t utilize the concept of the child as subjective and symbolic to express various materials for adult use, but rather it was special to children independently considered their emotions, age and personality and formally produced literary works. In the meantime, it goes without saying that the developments of psychology and the change of the human attitude towards the child and the independence of his personality played a critical role in attracting the attention of the writers and poets who addressed the child and everything belongs to him, disregarding his lateral and subordinate presence which had lasted for centuries. This would be more tangible as we get closer to the contemporary era like the 60's and 70's in which a great deal of children's literary works were produced.